A rare case of symptomatic bilateral pheochromocytoma - Akre, Ajinkya H.; Thorat, Santosh D. (International Journal of Research in Medical Sciences, 2024)
Pheochromocytoma with reported incidence of 2-8 per million, is a rare and special tumor with its own unique clinical and pathological features, originating from the amazingly intelligent neuroendocrine cells of chromaffin cells of the adrenal medulla. It may behave as ‘great masquerader’ and be sweet and predictable as a child, while at times act as a ‘treacherous murderer’ crashing and tearing everything in its path with fierce rage, the main cornerstone of the disease being surgical excision. Here, we report a rare case of middle aged female presenting with hypertensive crisis which necessitates intensive care unit (ICU) management where she responded well to anti-hypertensives and radiological investigations were suggestive of bilateral pheochromocytoma. The course of treatment consisted of array of investigations to ascertain the diagnosis before embarking on bilateral adrenalectomy keeping in mind the consequences of absence of adrenal and subsequent possibility of Nelsons syndrome, which we were able to treat successfully. Here we want to highlight the consideration of bilateral adrenal tumors as a differential diagnosis for suprarenal growths, subsequent surgical course and post-operative medical treatment highlighting the importance of mineralocorticoids and glucocorticoids for day to day functioning.